2015
DOI: 10.1186/s41016-015-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

The historical change of brainstem glioma diagnosis and treatment: from imaging to molecular pathology and then molecular imaging

Abstract: Understanding a process from shallow to deep is necessary for controlling and even curing diseases. The history of diagnosis and treatment of brainstem gliomas vividly reflects this process. The development of neuroimaging plays a great role in tumor treatment at different periods, including the period when brainstem gliomas were regarded as an homogenous incurable disease, and currently it is considered as an entity with high heterogeneity. Presently, it is not enough to just rely on the conventional neuroima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…DIPG presents a special challenge as their diffuse nature in the brainstem makes surgery not feasible [31,32]. Recent studies have shown MRI-guided stereotactic biopsy to be a safe and reliable method of molecularly characterizing a DIPG patient [33,34], and others were able to detect mutational status using cerebrospinal fluid-sourced tumor DNA [35].…”
Section: Standard Of Care Therapies In Phgg Including Dipgmentioning
confidence: 99%
“…DIPG presents a special challenge as their diffuse nature in the brainstem makes surgery not feasible [31,32]. Recent studies have shown MRI-guided stereotactic biopsy to be a safe and reliable method of molecularly characterizing a DIPG patient [33,34], and others were able to detect mutational status using cerebrospinal fluid-sourced tumor DNA [35].…”
Section: Standard Of Care Therapies In Phgg Including Dipgmentioning
confidence: 99%
“…[82][83][84][85] The development of molecular genetics and molecular imaging further promotes the progress of individualized diagnosis and therapy of BSG. 86 Prognosis and treatment depend upon the clinical symptoms and their duration as well as its location within the brainstem; the diffuse intrinsic type has the worst prognosis of all BSG, with median survival rarely exceeding 9 months. Focal midbrain tumors have a more indolent course with 80% of them showing 5 years free survival.…”
Section: Brainstem Gliomamentioning
confidence: 99%